TOLERANCE IN HISTORY NATIONAL MOVEMENT - Aldegonda Evangeline Pelealu; Aksilas Dasfordate; Darmawan Edi Winoto (Universitas Negeri Yogyakarta, 2021)
Tolerance has been widely practiced in the history of the nation's struggle. The value of this unity was not much discussed in the literature. When studying tolerance will relate a lot to religious tolerance and ethnicity. This article aims to examine the value of tolerance contained in the history of the nation's movement. The study used a qualitative approach with data collection through literature studies and expert interviews. Research shows that some movement organizations have practiced the value of tolerance. Budi Utomo's organization reflects tolerance in recruiting members from ethnic and group-based, changing to the national direction. Syarikat Islam was open to the presence of foreign traders, especially Chinese. Islamic organization, which has the concept of no coercion in religion. Tolerance is built-in Islam in a social context. Muhammadiyah, a socio-religious organization, can cooperate with various layers of society regardless of social status to achieve the Indonesian association's benefit that eliminates ego for national goals.